Peningkatan Hard Skill Dan Soft Skill Kelurahan Pamulang Timur Tangerang Selatan Menuju SDM Unggul - Angga Pratama; I Nyoman Marayasa; Suharni Rahayu (Jurnal Abdimas Tri Dharma Manajemen, 2025)
Based on the results of observations and discussions with friends, the priority problems faced by learning residents are divided into two aspects, namely: internal aspects and external aspects. The internal aspect is more likely to arise from the learning residents themselves because of their worries because they do not have skills and abilities in other fields such as not having a diploma. External aspects of inability to compete with other formal schools and also compete with other communities. The solution offered or proposed in this PKM activity is in accordance with the problems faced by partners, the solution for the internal aspect is to explore all the potential that exists in the learning citizens so that they are seen and accustomed to doing so, then motivate or foster the confidence of all learning residents to dare to appear or take part in every activity especially for self-improvement and External aspects The solutions offered to partners are providing entrepreneurial management training, including tips on becoming an entrepreneur, using cellphones, social networks to become business friends. In the management aspect, according to partner problems, the solution offered to partners in this Community Service is to provide assistance and counseling in managing a good lifestyle so that they are able to compete in the business world. Based on the proposed solution, the expected target in this PKM is the internal aspect. By completing equality education in Package C and getting a diploma, it indirectly becomes the main capital for growing self-confidence, because education is very important in the current era of globalization. In addition to participating in training so that other skills or abilities can be trained properly. External aspects After participating in partner training, it is hoped that they will be able to open new startups with the capital of their cellphones and be able to market through existing social networks. Management aspect, In accordance with the problems faced by partners, solutions are offered to friends In accordance with the problems faced by partners, solutions are offered to friends. Keywords: